2018
DOI: 10.1111/jre.12539
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long noncoding RNA‐associated competing endogenous RNA network in periodontitis

Abstract: These findings suggest that 6 mRNAs (HSPA4L, PANK3, YOD1, CTNNBIP1, EVI2B, ITGAL), 3 miRNAs (hsa-miR-125a-3p, hsa-miR-200a, hsa-miR-142-3p) and 3 lncRNAs (MALAT1, TUG1, FGD5-AS1) might be involved in the lncRNA-associated ceRNA network of periodontitis. This study sought to illuminate further the genetic and epigenetic mechanisms of periodontitis through constructing an lncRNA-associated ceRNA network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 47 publications
(54 reference statements)
2
48
0
Order By: Relevance
“…There are growing studies that suggest lncRNAs to play a pivotal role in disease pathogenesis by acting as ceRNAs to modulate the gene expression through sponging miRNAs [24,25]. Previous evidence pointed out that miR-142-3p is targeted by FGD5-AS1 as a part of the ceRNA network [11]. Moreover, miR-142-3p is considered as a mediator of inflammation and functions in regulating proinflammatory signalling pathways [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are growing studies that suggest lncRNAs to play a pivotal role in disease pathogenesis by acting as ceRNAs to modulate the gene expression through sponging miRNAs [24,25]. Previous evidence pointed out that miR-142-3p is targeted by FGD5-AS1 as a part of the ceRNA network [11]. Moreover, miR-142-3p is considered as a mediator of inflammation and functions in regulating proinflammatory signalling pathways [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed out that lncRNAs serving as competitive endogenous RNAs (ceRNAs) and sponging miRNAs in various diseases [12][13][14]. For example, FGD5-AS1 lncRNA, as a ceRNA, was proved to target miR-142-3p [11]. Based on these data, we investigated whether FGD5-AS1 regulates LPS-induced PDLC injury via sponging miR-142-3p.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…LncRNAs, miRNAs, and mRNAs interact with each other to form regulatory competitive endogenous RNA networks [6]. Recent studies have shown that there are signi cant differences in the expression pro le of miRNAs and lncRNAs between in ammatory and healthy gingival tissue in patients with periodontitis [7]. However, the ceRNA network involved in the pathogenesis of peri-implantitis has not been reported by scholars.…”
Section: Introductionmentioning
confidence: 99%